2014
DOI: 10.1007/s40544-014-0048-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of pulsed magnetic field pre-treatment of AISI 52100 steel on the coefficient of sliding friction and wear in pin-on-disk tests

Abstract: Disc specimens manufactured from commercial bearing rollers (AISI 52100 steel, 62−63 HRC) in initial state and after pre-treatment by pulsed magnetic field (PMF) with a magnetic field strength of 1−7 MA/m were tested with sunflower oil using pin-on-disk apparatus. According to the obtained results the treatment causes a reduction in the coefficient of friction and wear. To explain the results, nano-and microhardness tests as well as optical and atomic force microscopy were used. Reasons of the effect of PMF on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 18 publications
0
13
0
Order By: Relevance
“…In the latter investigation [3], tests for high-speed steel drills that had undergone pulsed magnetic field treatment were reported to result in an increase in the number of drilled holes by about 15% compared to drills in the untreated condition. In another study conducted by Babtuskyi et al [4] it was demonstrated that the application of pulsed magnetic field treatment to AISI 52100 steel led to a reduction in the sliding friction properties by 13%. Similar findings have been reported by Xi, Xia [5] who studied the effect of pulsed magnetic field treatment on the tribological behaviour of AISI 1045 steel and reported reduction in the size of wear tracks and in the value of the coefficient of friction as a result.…”
Section: Introductionmentioning
confidence: 97%
“…In the latter investigation [3], tests for high-speed steel drills that had undergone pulsed magnetic field treatment were reported to result in an increase in the number of drilled holes by about 15% compared to drills in the untreated condition. In another study conducted by Babtuskyi et al [4] it was demonstrated that the application of pulsed magnetic field treatment to AISI 52100 steel led to a reduction in the sliding friction properties by 13%. Similar findings have been reported by Xi, Xia [5] who studied the effect of pulsed magnetic field treatment on the tribological behaviour of AISI 1045 steel and reported reduction in the size of wear tracks and in the value of the coefficient of friction as a result.…”
Section: Introductionmentioning
confidence: 97%
“…Among the steels for aerospace bearings, M50 steel is widely used because of its excellent dimensional stability and hardness retention in high-temperature environments [2]. As bearings inevitably suffer from wear during operation, wear failure caused by surface abrasion is one of the main failure modes for aerospace bearings [3]. Therefore, it is necessary to explore a surface strengthening technique to effectively improve the wear resistance of M50 steel.…”
Section: Introductionmentioning
confidence: 99%
“…During recent years, there has been growing interest in the use of magnetic fields to improve the mechanical properties and the tribological behaviour of metallic alloys [2,[12][13][14][15][16][17]. While most of these investigations conducted tribological tests in the presence of a magnetic field, Xi et al [17] examined the effect of pulsed magnetic field treatment on the tribological behaviour of AISI 1045 steel.…”
Section: Introductionmentioning
confidence: 99%
“…While most of these investigations conducted tribological tests in the presence of a magnetic field, Xi et al [17] examined the effect of pulsed magnetic field treatment on the tribological behaviour of AISI 1045 steel. It was reported that the coefficient of friction decreased by 16.4% after the application of a pulsed magnetic field of 320 Gs about 30 s prior to the friction wear test. Xi et al [17] attributed the improvements of the tribological properties to increased dislocation density and refined ferrite.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation